Human Resource Competence and Digital Payment Adoption in MSMEs: An Extended TAM Framework - Arifhan Ady DJ; Anis Anshari Mas'ud; Andi Putri Tenriyola (Jurnal Manajemen dan Kewirausahaan, 2026)
The current research explores the primary drivers influencing the implementation of electronic payment mechanisms within small-scale business sectors in West Sulawesi, Indonesia. By integrating an expanded Technology Acceptance Model (TAM), this paper examines not only the direct effects of perceived utility and usability but also the functional role of human resource competence as a moderating factor. A cross-sectional quantitative research design was applied. Survey data were collected from 250 MSME owners/managers in West Sulawesi using purposive sampling. The conceptual model, which includes direct and moderating effects, employs purposive sampling and distributes questionnaires. Findings indicate that perceptions of usefulness and ease of use are robust determinants of digital transaction adoption, aligning with established TAM frameworks. Crucially, the study identifies that human resource competence significantly strengthens the impact of perceived usability on actual adoption behavior, suggesting that internal expertise acts as a catalyst for technological integration. This work provides a substantial theoretical advancement by being among the initial empirical efforts to incorporate human capital dimensions as a moderator within the TAM to clarify digital payments by MSMEs in developing countries.